2012
DOI: 10.1128/aem.06501-11
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Increases Xylella fastidiosa Surface Attachment, Biofilm Formation, and Twitching Motility

Abstract: Xylella fastidiosa is a plant-pathogenic bacterium that forms biofilms inside xylem vessels, a process thought to be influenced by the chemical composition of xylem sap. In this work, the effect of calcium on the production of X. fastidiosa biofilm and movement was analyzed under in vitro conditions. After a dose-response study with 96-well plates using eight metals, the strongest increase of biofilm formation was observed when medium was supplemented with at least 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
134
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(152 citation statements)
references
References 53 publications
15
134
0
3
Order By: Relevance
“…Previous research has shown that increasing amounts of calcium disable Bap-mediated biofilm formation and intercellular adhesion of Staphylococcus aureus (1). However, recent reports indicate that calcium promotes biofilm formation in other microorganisms, such as Xyllela fastidiosa or Vibrio vulnificus (4,7). Therefore, calcium may modulate biofilm formation in opposite ways in different bacteria, but the molecular basis for its role remains unclear.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Previous research has shown that increasing amounts of calcium disable Bap-mediated biofilm formation and intercellular adhesion of Staphylococcus aureus (1). However, recent reports indicate that calcium promotes biofilm formation in other microorganisms, such as Xyllela fastidiosa or Vibrio vulnificus (4,7). Therefore, calcium may modulate biofilm formation in opposite ways in different bacteria, but the molecular basis for its role remains unclear.…”
mentioning
confidence: 87%
“…Calcium has been related to a variety of biological processes in bacteria (4,7,10), but its role in biofilm development is somewhat controversial. Previous research has shown that increasing amounts of calcium disable Bap-mediated biofilm formation and intercellular adhesion of Staphylococcus aureus (1).…”
mentioning
confidence: 99%
“…Growth rates were calculated as the slope of line obtained by natural logtransformed growth values at the exponential growth phase (approximately 1 to 4 days) using the formula {rate = [ln (OD day 4) -ln (OD day1)]/time}. Biofilm was quantified using the crystal violet assay, as previously described (Cruz et al 2012), at the end of the growth curve experiment (day 8). Settling rate, as a measure of cell-to-cell attachment, was determined by measuring OD 600 of a cell suspension in a cuvette when cells appeared to settle exponentially (5 to 30 min postinoculation [mpi]).…”
Section: Methodsmentioning
confidence: 99%
“…Adding metals to the medium (Ca, Co, Cu, Fe and so on) [53], exposing bacteria to tissue cells it interacts with and feels tropism towards [54] as our work, are some methods employed in order to study and promote cell adhesion and twitching displacement. That is it, Phdp strain PP3 showed a slightly better displacement in culture media with a lot of cells; strains 94/99, DI21 and ATCC 17911 too, but a lower amount of added cells was enough and better; however, for the strain C2, media with or without cell debris did not make difference.…”
Section: Discussionmentioning
confidence: 99%